Five Years With Dolutegravir Plus Lamivudine as a Switch Strategy: Much More Than a Positive Finding. (1st November 2021) - Ciccullo, Arturo; Borghi, Vanni; Giacomelli, Andrea; Cossu, Maria Vittoria; Sterrantino, Gaetana; Latini, Alessandra; Giacometti, Andrea; De Vito, Andrea; Gennari, William; Madeddu, Giordano; Capetti, Amedeo; d'Ettorre, Gabriella; et al.
Abstract : Background: Results from clinical trials and observational studies suggest that dolutegravir plus lamivudine could be an effective and well-tolerated option for simplification in HIV-1–positive patients. We aimed to assess long-time efficacy and safety in our multicenter cohort. Methods: This was a retrospective study enrolling HIV-1–infected, virologically suppressed patients switching to dolutegravir + lamivudine. We performed survival analysis to evaluate time to virological failure (VF, defined by a single HIV-RNA ≥1000 copies/mL or by 2 consecutive HIV-RNA ≥ 50 copies/mL) and treatment discontinuation (defined as the interruption of either 3TC or dolutegravir), assessing predictors via Cox regression analyses. Results: Seven-hundred eighty-five patients were considered for the analysis: 554 were men (70.6%), with a median age of 52 years (interquartile range 45–58 years). Estimated probabilities of maintaining virological suppression at weeks 96, 144, and 240 were 97.7% (SD ±0.6), 96.9% (SD ±0.8), and 96.4% (SD ±0.9), respectively. A non-B HIV subtype ( P = 0.014) and a previous VF ( P = 0.037) resulted predictors of VF. We did not observe differences in probability of VF in people living with HIV with an M184V resistance mutation ( P = 0.689); however, in a deeper analysis, M184V mutation was a predictor of VF ( P = 0.038) in patients with time of virological suppression <88 months. Estimated probabilities of remaining on study regimen at 96, 144, and 240 weeks were 82.9% (SD ±1.4), 79.7% (SD ±1.6) and 74.3% (SD ±2.2), respectively. Conclusions: Our findings show the long-term efficacy and tolerability of dolutegravir plus lamivudine in virologically suppressed patients.